Present status and problem confrontation of oilseed cultivation in southwest region of Bangladesh (Journal of the Bangladesh Agricultural University, 2018)
The present piece of research was conducted to explore the present status and problem confrontation of oilseed cultivation. Besides, relationship of the selected characteristics of the respondents with their problem confrontation was explored. This study was conducted at three selected villages namely Fultola, Debitola and Hetalbunia of Batiaghata upazila. Data were collected from purposive randomly selected 82 respondents during the period of 07 to 27 May, 2017. Appropriate scales were used to measure the variables of the study. Correlation test was used to ascertain the relationship between the personal characteristics with the faced problems. Average age of the respondents was 50.43 years. Around two-third (63.4 percent) of the respondents belonged to nuclear family with small to medium (65.9 percent) family size with an average of 5.87 years of schooling. Most (98.7 percent) of the respondents had scanty land ownership. All of them had oilseed cultivation experience and 57.3 percent had organizational participation. Their average annual income was 1,06,122 Tk. Three-fourth (75.6 percent) of the respondents had medium extension contact and about two-third (69.5 percent) had low cosmopoliteness. Among the respondents 68.3 percent had high knowledge, 81.7 percent had favorable attitude, and among oilseed sesame ranked first position in case of cultivation practice. Water logging, salinity and lack of improved technology for planting and harvesting ranked 1st, 2nd and 3rd position, respectively, among the problems. Annual income and attitude had negative significant relationship with problem confrontation. Respondents had favorable attitude towards oilseed cultivation. This attitude may be a tool for the oilseed farmers to increase the oilseed cultivation status in the study area.J. Bangladesh Agril. Univ. 16(2): 198-207, August 2018